Toxicity of Pesticides - O. Norman Nesheim; Frederick M. Fishel; Mark Mossler (EDIS)
This document describes how pesticides work on living things, so you can learn to reduce or eliminate exposure. This document is PI-13, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date July 1993. Revised July 2005.